2009
DOI: 10.1093/bja/aep131
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac electrophysiological effects of remifentanil: study in a closed-chest porcine model

Abstract: Remifentanil depresses sinus node function and most parameters of AV nodal function. This contributes to an explanation for clinical observations of remifentanil-related severe bradyarrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
1
32
1
1
Order By: Relevance
“…The complication rates in this study were similar to those observed by other authors 1,3,16,29,30 and were similar for both groups. The incidence of recurrence (outcome) of AF in three months was equal in both G1 and G2.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The complication rates in this study were similar to those observed by other authors 1,3,16,29,30 and were similar for both groups. The incidence of recurrence (outcome) of AF in three months was equal in both G1 and G2.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 91%
“…Zaballos et al 16 concluded that the hemodynamic effects of remifentanil are associated with decreased vagal tone, being able to produce marked decrease in heart rate.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, new anaesthetics are constantly sought, and the effects of the available anaesthetic drugs are being widely studied. The most common drugs used to anesthetise pigs include midazolam, azaperon, fentanyl, droperidol, ketamine and barbiturates (5,19,36). Alpha-2 adrenergic agonists, which are commonly used in companion animals, are rarely used in laboratory animals prior to cardiovascular procedures, because they reduce the blood pressure and heart rate.…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…After obtaining written, informed consent from each patient and/or their family, patients were divided into 3 groups according to a previous study by Zaballos et al [17]: 1) control group (group C, N=20), in which all patients received a single 20-ml injection of saline solution prior to mECT; 2) low-dose remifentanil group (group L, N=20), in which all patients received a single 20-ml injection of saline solution containing 0.5 μg/kg of remifentanil prior to mECT; and 3) high-dose remifentanil group (group H, N=20), in which all patients received a single 20-ml injection of saline solution containing 1.0 μg/kg of remifentanil prior to mECT.…”
Section: Patient Classificationmentioning
confidence: 99%